Chemical Mechanisms and Their Applications in the Goddard Earth Observing System (GEOS) Earth System Model. (26th December 2017) - Nielsen, J. Eric; Pawson, Steven; Molod, Andrea; Auer, Benjamin; da Silva, Arlindo M.; Douglass, Anne R.; Duncan, Bryan; Liang, Qing; Manyin, Michael; Oman, Luke D.; Putman, William; Strahan, Susan E.; et al.
Abstract: NASA's Goddard Earth Observing System (GEOS) Earth System Model (ESM) is a modular, general circulation model (GCM), and data assimilation system (DAS) that is used to simulate and study the coupled dynamics, physics, chemistry, and biology of our planet. GEOS is developed by the Global Modeling and Assimilation Office (GMAO) at NASA Goddard Space Flight Center. It generates near‐real‐time analyzed data products, reanalyses, and weather and seasonal forecasts to support research targeted to understanding interactions among Earth System processes. For chemistry, our efforts are focused on ozone and its influence on the state of the atmosphere and oceans, and on trace gas data assimilation and global forecasting at mesoscale discretization. Several chemistry and aerosol modules are coupled to the GCM, which enables GEOS to address topics pertinent to NASA's Earth Science Mission. This paper describes the atmospheric chemistry components of GEOS and provides an overview of its Earth System Modeling Framework (ESMF)‐based software infrastructure, which promotes a rich spectrum of feedbacks that influence circulation and climate, and impact human and ecosystem health. We detail how GEOS allows model users to select chemical mechanisms and emission scenarios at run time, establish the extent to which the aerosol and chemical components communicate, and decide whether either or both influence the radiative transfer calculations. A variety of resolutions facilitates research on spatial and temporal scales relevant to problems ranging from hourly changes in air quality to trace gas trends in a changing climate. Samples of recent GEOS chemistry applications are provided. Plain Language Summary: This manuscript describes the current state of the atmospheric chemistry components and mechanisms in NASA's Goddard Earth Observing System (GEOS) Earth System Model (ESM) and provides an overview of its Earth System Modeling Framework (ESMF)‐based software infrastructure. Its purposes are to familiarize atmospheric chemical modelers with GEOS's hierarchy of components and the connections between them, review the elements of the Modeling Analysis and Prediction Layer (MAPL) that are particularly useful for chemical simulations, and describe the functionality that each of the several chemical components provides. Following the infrastructure discussion, a number of practical applications highlight the wide variation of atmospheric chemistry problems to which GEOS can be applied. They demonstrate that GEOS is a platform for leading‐edge chemical data assimilation, simulation, forecasting, and research that is engineered to meet the demands of NASA's Earth Science mission now and in the future. Key Points: The GEOS Earth System Model's architecture is based on ESMF and the GMAO's middleware layer called MAPL GEOS uses a common code base of interchangeable chemical components for data assimilation, forecasting, and research GEOS is applied to atmospheric chemistry topics ranging from diurnal air quality variations to climate change